2021
DOI: 10.1111/tmi.13701
|View full text |Cite
|
Sign up to set email alerts
|

Stability of healthcare quality measures for maternal and child services: Analysis of the continuous service provision assessment of health facilities in Senegal, 2012–2018

Abstract: Objective High‐quality healthcare is essential to ensuring maternal and newborn survival. Efficient measurement requires knowing how long measures of quality provide consistent insight for intended uses. Methods We used a repeated health facility assessment in Senegal to calculate structural and process quality of antenatal care (ANC), delivery and child health services in facilities assessed 2 years apart. We tested agreement of quality measures within facilities and regions. We estimated how much input‐adjus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 42 publications
(51 reference statements)
0
11
1
Order By: Relevance
“…Our framework provides a tool to identify the sources of variability in each readiness and 16 ; yet in the present study, we found substantial random temporal variations in both process and readiness of care metrics when considering all facilities assessed in each wave, which may reflect both sampling variability and true changes in the quality metrics.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…Our framework provides a tool to identify the sources of variability in each readiness and 16 ; yet in the present study, we found substantial random temporal variations in both process and readiness of care metrics when considering all facilities assessed in each wave, which may reflect both sampling variability and true changes in the quality metrics.…”
Section: Discussionmentioning
confidence: 64%
“…Practically, the complete time-series of these modelled healthcare quality metrics could be used to improve subnational estimates of effective coverage. To date, effective coverage-a key metric to monitor progress towards universal health coverage in LMICs (Ng et al ., 2014; Leslie et al ., 2017a), has been calculated by combining estimates from health facility and household surveys, potentially conducted in different years (Carter et al ., 2021); however, this approach can prove problematic if healthcare quality changes rapidly over time (Kruk et al ., 2017; Leslie et al ., 2022). Yearly subnational estimates of healthcare quality metrics mitigate this problem by computing effective coverage from temporally aligned facility and population estimates, with associated uncertainty.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations